Analisa Pengaruh Total Quality Manajemen Terhadap Kepuasan Konsumen - Megawati, Risky Ega; Pratiwi, Ni Made Ida; Maruta, IGN Anom (Jurnal Dinamika Administrasi Bisnis, 2017)
Â UD. Rizky Barokah is one forest honey producers headquartered in Surabaya. . With the growing number of entrepreneurs honey from year to year shows the business environment in the increasingly competitive field of honey. Competitive business environment requires all employers to apply the quality of services in addition to providing the best product quality through the application of TQM albeit with different levels in an effort to create customer satisfaction. The purpose of this study was to: "Determine the influence of TQM on consumer satisfaction UD.Rizky Barokah"Total Quality Management (TQM) is a management approach that is trying to achieve and sustain long-term success to meet customer satisfaction as one of its objectives. . With high product quality and low price, competitive position in the market will increase. The following series of events will help organizations transform and achieve the purpose of profit and grow more easily. In addition, workers will have job security, which will create satisfaction in the workplace (Basterfiel, 2011, 2) According to Krajewski (2005, 196) consumers are satisfied when their expectations for a product or quality are met. Sometimes, consumers use quality requirements common to describe the level of their satisfaction with a product or service. Analysis of total quality management at UD. Rizky Barokah indicate the category of "very good". It is shown from the results of the interview, the application of total quality management is based on three pillars, namely human resources responsive, value and ease of contacting the seller. Of the three pillars researchers found the results were realistic about the application of total quality management concepts UD. Rizky Barokah.Â Keywords: TQM, Kualitas, Kepuasan Konsumen, Penerapan TQM untuk UKM